GENETIC DIVERSITY, AGRONOMICAL CHARACTERISTICS AND RESISTANCE TO BLUE DISEASE IN SOME LOCAL AND INTRODUCED COTTON CULTUVARS - Nguyệt, Nguyễn Thị Minh (Vietnam Journal of Biotechnology, 2011)
The genetic diversity among 49 local and infroduced  cotton cultivars belonging to Gossypium hirsutum L., Gossypium barbadense L.  and  Gossypium arboretum L.  were  investigated  using  50  SSR  markers,  which provided  128  alleles.  The  genetic  relationships  among  49  cotton  genot)^es  were  examined  using  SM coefficient  to  compute  the  similarity  matrices.  UPGMA  analysis  was  performed  and  dendrogram  was constructed. The genetic similarity ranged from 0.48 to 0.97 with an average of 0.8 indicated sufficient  genetic diversity  does  exist  within  the  cotton  collection.  Dendrogram  clustered  the  49  cotton  genotypes  into  three distinct groups: one of 21 G. hirsutum L. genotypes, one of 16 G. barbadense L. genotypes, and the other of 12 G. arboretum  L. genetypes, that are agreement  with the traditional  taxonomic arrangement  of these cultivars. Genetic  similarities  among  each  group  ranged  from  0.86  to  0.96.  More  genetic  diversity  was  observed  in Gossypium hirsutum L.  than  Gossypium barbadense L.  and  Gossypium arboretum L..  Morphological  and agronomical  characteristics  were  also  evaluated  under  field  condition  in  2007  indicated  that  Gossypium hirsutum L.  cultivars  yielded  higher,  but  produced  lower  fiber  quality,  while  Gossypium barbadense L. cultivars  have  lower  yield  but  higher  fiber  quality.  The  screening  of  cotton  blue  disease  under  glass  house condition indicated that  100% cultivars oi Gossypium hirsutum L. and Gossypium barbadense L. groups were susceptible to blue disease. In  Gossypium  arboretum L. group, there was only Co Nghe An variety  and  four elite  lines  developed  from  Co Nghe  An  showed  resistance  to blue  disease.  These  results  could  be handy  in parental selection tool for mapping and breeding for cotton blue disease resistance